2022
DOI: 10.1093/schbul/sbac067
|View full text |Cite
|
Sign up to set email alerts
|

Tool-use Extends Peripersonal Space Boundaries in Schizophrenic Patients

Abstract: Background and Hypothesis A primary disruption of the bodily self is considered a core feature of schizophrenia (SCZ). The “disembodied” self might be underpinned by inefficient body-related multisensory integration processes, normally occurring in the peripersonal space (PPS), a plastic sector of space surrounding the body whose extent is altered in SCZ. Although PPS is a malleable interface marking the perceptual border between self and others, no study has addressed the potential alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 58 publications
4
25
0
Order By: Relevance
“…Thus, RTs were entered in a repeated-measures ANOVA with sensory modality (multisensory, unisensory) as the within-subjects factor. The ANOVA showed a significant main effect of sensory modality (F (1,20) = 55.77, p < 0.001, η 2 p = 0.74), showing that multisensory RTs (multisensory: M = 521.83, SE = 12.58) were faster than the unisensory tactile ones (unisensory: M = 604.11, SE = 16.64), demonstrating a clear multisensory facilitation effect in line with previous studies e.g., [ 9 , 46 ].…”
Section: Data Analysis and Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, RTs were entered in a repeated-measures ANOVA with sensory modality (multisensory, unisensory) as the within-subjects factor. The ANOVA showed a significant main effect of sensory modality (F (1,20) = 55.77, p < 0.001, η 2 p = 0.74), showing that multisensory RTs (multisensory: M = 521.83, SE = 12.58) were faster than the unisensory tactile ones (unisensory: M = 604.11, SE = 16.64), demonstrating a clear multisensory facilitation effect in line with previous studies e.g., [ 9 , 46 ].…”
Section: Data Analysis and Resultssupporting
confidence: 91%
“…Lastly, to estimate the individual boundary of PPS, PSE (point of subjective equality) of the psychometric function describing visuo-tactile RTs as a function of visuo-tactile distance was measured via the Spearman–Karber (SK) method [ 47 , 48 ] in line with recent studies on PPS [ 9 , 29 , 46 ]. For more specific details about the implemented procedure, please refer to the Supplementary Materials (Section 2) .…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two points of our results are worth pointing out. First, the general increase in the distance due to simple tool use gives further support to the motor plasticity attributed to the representation of the space around the body conceived as reaching space (e.g., [ 63 , 64 , 65 ]).The active use of a long tool extends the representation of the reachable space by ideally expanding the point at which one might act and by confirming a close relationship between the arm action capabilities and reaching space (e.g., [ 11 , 18 , 42 , 44 , 45 , 46 , 47 , 63 , 64 , 65 , 66 ]). Moreover, in line with the existent data, tool use modifies the reaching distance towards a potentially relevant social stimulus (e.g., [ 39 , 40 ]).…”
Section: Discussionmentioning
confidence: 97%
“…However, further studies are needed to understand to what extent and under what conditions these two spaces may reveal similar behavioural displays. Furthermore, many studies have identified alterations of the representation of the space around the body in neurological [ 70 ], psychopathological [ 64 , 71 , 72 ] or autistic [ 19 ] patients. Therefore, in-depth knowledge of the mechanisms of sharing or segregation between action space and interpersonal social space may potentially suggest new ways to improve or rehabilitate the functions of representing the space around our bodies.…”
Section: Discussionmentioning
confidence: 99%